Biological Determinants of Adolescent Mental Health - Wardiyah Daulay; S. Kep; Ns.; M. Kep (Journal of the Dow University of Health Sciences)
Health is a holistic concept encompassing physical, mental, and social well-being. An individual cannot be deemed truly healthy without mental wellness. According to the World Health Organization (WHO), mental health is not merely the absence of mental disorders; rather, it is a state in which individuals realize their potential, can cope with the normal stresses of life, work productively, and contribute to their community.1 Good mental health enables individuals to build positive relationships, accept themselves and others, and manage emotional challenges effectively. In adolescents, mental health is a particularly critical concern. Data from the Indonesian National Adolescent Mental Health Survey (NAMHS) report that approxima-tely one in three adolescents (34.9%) experience mental health problems, while one in ten (5.5%) are affected by a diagnosable mental disorder.2 These alarming figures underscore that adolescent mental health is not only a psychological or educational issue but a major public health priority.